Rural poverty unperceived: problems and remedies: a background study for world development report, 1980 (Washington, 1984)
This paper argues that in developing countries poor rural people and rural poverty generally are underperceived or misperceived by those who are themselves neither poor nor rural. This process can be understood, first, in terms of the obstacle presented by global cores and peripheries of knowledge, with poor, weak, rural people at the peripheries and rich, powerful urban-based professionals at the cores; and, second, in terms of the obstacle raised by the integrated nature of rural poverty, especially by the isolation of the poor. A major associated influence on, or obstacle to, the perceptions of urban-based outsiders is that of rural development tourism -- the phenomenon of the brief rural visit. It is widely practised but little analyzed. These three obstacles to perception are discussed in Section II.
Keywords: Poverty